Forgiveness and Loneliness in Peer-Victimized Adolescents - León-Moreno, Celeste (Journal of interpersonal violence, 2021)
The purpose of the present study was to analyze the relationships between forgiveness, motivations for revenge, avoidance, and benevolence; loneliness, emotional loneliness and positive subjective evaluation of the social network; and peer victimization in schools, relational, overt physical, and overt verbal, based on gender. A battery of instruments was administered to 617 Spanish students (50.7% boys and 49.3% girls), aged between 10 and 16 years (M = 13.04 years, SD = 1.80 years) from primary and secondary education. A multivariate analysis of variance and a multiple block regression for data analysis was used. Study results revealed that the most victimized students showed greater motivation for revenge and avoidance, as well as a greater perception of emotional loneliness and less positive subjective evaluation of their social network. In addition, the findings obtained in the regression analysis (stepwise) indicated that being a boy between 11 and 13 years old and having a high level of emotional loneliness and high avoidance motivation were the most important predictors of peer victimization. Finally, the findings and their possible implications in the design of intervention projects that encourage forgiveness in interpersonal conflicts and integration in social networks as preventive strategies of peer victimization were discussed.